Dependability analysis of safety critical and control systems of NPP - Kamal Kaur R.; Kumar Singh L.; Singh P. (My University, 2025)
UML is a proven and simple modeling language to capture all the functional requirements of the system. Petri net is a powerful tool to analyze structural and behavioral properties of the system for evaluating the non-functional requirements (i.e., reliability, availability, safety, security, and performability) of safety–critical and control systems. However, transforming system requirements into a Petri net (PN) model, directly, may not be understood by all the stakeholders and hence may lead to a model with incomplete requirements. This work proposed a framework to transform UML model into a PN model that can be used to analyze the dependability (i.e., non-functional requirements) of critical systems. The methodology has been implemented for the development of a tool. The applicability of the proposed mechanism and correctness of the developed tool has been validated by applying it on safety critical and control systems of the Nuclear Power Plant (i.e., sub-system of Digital Feed-water Control System (DFWCS). © 2022 Elsevier B.V.